The impact of policy awareness: Evidence from vehicle choices response to fiscal incentives - Davide Cerruti; Claudio Daminato; Massimo Filippini (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
Isolating the role of limited knowledge, psychological frictions and policy characteristics is key when evaluating a public program and designing future policies. This paper explores the role of awareness about the presence of fiscal programs in determining their impact on individual choices. Our identification strategy exploits quasi-experimental variation in the introduction of fiscal incentives aimed at promoting the purchase of energy efficient vehicles, and a direct measure of policy awareness at the individual level. We find an important impact of awareness on consumers' vehicle choices, highlighting that limited awareness may represent a critical barrier to the effectiveness of public programs.
Keywords: D12; D83; H23; H31; Q48; 330; Policy awareness; Fiscal programs; Environmental taxation; Vehicle choices